Synthesis and characterization of hard kappa carrageenan capsule through glyoxal and glyoxylic acid crosslinking - Intan Lyana, Ahmad (2014)
This research is about the synthesis and characterization studies of the hydrogel for hard kappa carrageenan capsule through glyoxal and glyoxylic acid crosslinking. In this work, kappa carrageenan hydrogel were prepared by chemical crosslinking using glyoxal and glyoxylic acid as the crosslinking agent and hydrochloric acid (HCl) as the catalyst. The purpose of this study is to select the best crosslinker material to develop hard kappa carrageenan capsule that can improve its propertis through molecular recognition approach by using crosslink technique. Aqueous kappa carrageenan (3% w/v) was reacted with a certain amount of glyoxal and glyoxylic acid (25%) respectively and HCl (0.1N) at 40°C. After 30 minutes of reaction, the homogenous solution was cooled at room temperature producing gel form. The gel was soaked in the ethanol to remove unreacted residue or chemicals. The obtained hydrogel was air dried at room temperature to constant weight. The FTIR spectra, DSC, TGA and the value of swelling ratio of obtaining hydrogel showed that kappa carrageenan could be crosslinked using glyoxal or glyoxylic acid. Based on the FTIR, there were some functional group detected showed that the crosslinker and kappa carrageenan was successsful crosslinked. There were no significant differences in the swelling degree of hydrogel synthesized in the distilled water and all buffer solution. The crosslinking with a certain amount of glyoxal and HCl may be produce hydrogel with a lower swelling degree. The kappa carrageenan hydrogel was found to be pH sensitive, indicating a high potential to be used in drg delivery polymer system